Clinical utility of comprehensive genomic profiling tests for advanced or metastatic solid tumor in clinical practice. Issue 12 (29th September 2022) - Ida, Hanae; Koyama, Takafumi; Mizuno, Takaaki; Sunami, Kuniko; Kubo, Takashi; Sudo, Kazuki; Tao, Kayoko; Hirata, Makoto; Yonemori, Kan; Kato, Ken; Okusaka, Takuji; Ohe, Yuichiro; et al.
Abstract: Previous clinical trials indicate that 10%–25% of patients received genomically matched therapy after comprehensive genomic profiling (CGP) tests. However, the clinical utility of CGP tests has not been assessed in clinical practice. We assessed the clinical utility of CGP tests for advanced or metastatic solid tumor and determined the proportion of patients receiving genomically matched therapy among those with common and non‐common cancers. From August 2019 to July 2020, a total of 418 patients had undergone CGP tests, and the results were discussed through the molecular tumor board at our site. The median age of patients was 57 (range: 3–86) years. Colorectal cancer was the most common, with 47 (11%) patients. Actionable genomic alterations (median 3, range: 1–17) were identified in 368 (88.0%) of 418 patients. Druggable genomic alterations were determined in 196 (46.9%) of 418 patients through the molecular tumor board. Genomically matched therapy was administered as the subsequent line of therapy in 51 (12.2%) patients, which is comparable to the proportion we previously reported in a clinical trial (13.4%) ( p = 0.6919). The proportion of patients receiving genomically matched therapy was significantly higher among those with common cancers (16.2%) than non‐common cancers (9.4%) ( p = 0.0365). Genomically matched therapy after the CGP tests was administered to 12.2% of patients, which is similar to the proportion reported in the previous clinical trials. The clinical utility of CGP tests in patients with common cancers greatly exceeded that in patients with non‐common cancers. Abstract : Genomically matched therapy after comprehensive genomic profiling (CGP) tests was administered to 12.2% of patients in clinical practice. We demonstrated the clinical utility of CGP tests in clinical practice, particularly among those with common cancers who received genomically matched therapy more frequently than those with non‐common cancers.